Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum Dan Setelah Kombinasi Bisnis (Studi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia) - Ningsih, Nadya Ayu; Kurniawati, Tri (Jurnal Salingka Nagari, 2024)
This study aims to analyze and explain the differences in financial performance before and after business combinations in companies listed on the Indonesia Stock Exchange (IDX). The type of research used is quantitative research. The research technique is comparative statistics. The data source is secondary with a sampling method using Saturated Samples with a sample size of 40 samples. Data testing was conducted using the Paired T-Test and Wilcoxon Sign Rank Test calculated using Statistical Package Social Sciences (SPSS) 21 software. The results of the hypothesis test that had been conducted showed that there were 14 ratios that did not experience significant differences, namely Current Ratio (CR), Quick Ratio (QR), Cash Ratio (CsR), Cash Turnover Ratio (RPK), Inventory To Net Working Capital, Debt to Asset Ratio (DAR), Long Term Debt to Equity Ratio (LTDtER), Debt to Equity Ratio and Fixed Charge Coverage (FCC), Net Profit Margin, Gross Profit Margin, Return On Investment (ROI), Return On Equity (ROE) and Earnings Per Share (EPS). Meanwhile, the ratio that experienced a significant difference after the business combination was the Timed Interest Earned